THE IMPACT OF FAKE NEWS ON PUBLIC OPINION FORMATION AND THE LIMITS OF STATE INTERVENTION (CIPEEX, 2025)
ABSTRACTThe advancement of information technologies has increased the circulation of data, but also intensified the propagation of so-called fake news. This phenomenon, marked by the deliberate dissemination of false or distorted information, directly impacts the formation of public opinion and interferes with democratic processes, such as elections.This study aims to investigate how fake news shapes voters' perceptions and the extent to which the State can intervene without violating constitutional guarantees, such as freedom of expression. The research uses a qualitative approach, based on a literature review and documentary analysis,seeking to reflect on the role of digital platforms, the challenge of regulation, and the risks of censorship.It concludes that combating disinformation requires coordinated actions between the State, civil society, and the private sector, ensuring transparency, accountability, and media literacy as pillars of an informed democracy.INTRODUCTIONIn recent years, the phenomenon of fake news has gained centrality in the global public debate, especially given its role in the 2016 United States presidential election, the 2018 and 2022 Brexit referendum, and the Brazilian elections in 2018 and 2022. In Brazil, the population's vulnerability to misinformation is heightened by a poorly regulated digital environment, low media literacy, and socioeconomic factors that make it difficult to verify information.It should be noted that disinformation operates through emotional manipulation techniques, appealing to prior beliefs and prejudices, which makes its dismantling more complex than simple factual denial (Rodrigues; Banone; Mielli, 2020).This study aims to investigate the impacts of fake news on public opinion formation, focusing on the risks to the integrity of democratic processes and the constitutional limits on state intervention. The following question is posed: how can the State act to combat disinformation without violating the constitutional principles of freedom of expression and political pluralism?The justification for this study lies in the urgency of establishing legal frameworks that tackle the problem with a balance between protecting fundamental rights and preserving the democratic order. The relevance of this topic grows given the realization that informational manipulation compromises free and informed voting, the foundation of any democratic regime.METHODThe research adopted a qualitative and exploratory approach, based on a literature review and document analysis. Works by renowned authors in the fields of communication, constitutional law, and political science were consulted, as well as institutional reports from the Superior Electoral Court (TSE), the Federal Supreme Court (STF), the United Nations (UN), and the Inter-American Commission on Human Rights.The methodology included a hermeneutic analysis of legal and regulatory documents, with an emphasis on case law related to the regulation of internet content and the limits of state censorship.The triangulation of sources sought to ensure greater robustness in the analysis, expanding the debate on the contemporary challenges of information regulation.RESULTS AND DISCUSSION/EXPERIENCE REPORTIt is observed that fake news operates based on a logic of viralization, encouraged by digital platform algorithms that prioritize engagement over informational veracity (França; Camarão, 2022). This model fosters the creation of "information bubbles," in which pre-existing views are reinforced and contact with divergent perspectives is reduced, contributing to radicalization and the formation of ideological comfort zones.In Brazil, TSE reports indicate that, in the 2018 and 2022 elections, misinformation content circulated on networks such as WhatsApp, Telegram, and Facebook with greater speed and reach than news verified by traditional media outlets. Disinformation largely exploited religious discourse, conspiracy theories, and anti-political sentiments, fostering polarization and undermining trust in institutions (Carvalho Almeida, 2020).The intervention of the Federal Supreme Court (STF), which ordered the suspension of profiles and the removal of content in the context of investigations related to so-called "digital militias," sparked intense debate. Although grounded in the need to protect the democratic order, the judicial action raised concerns about the possibility of prior censorship, which is expressly prohibited by Article 220, §2, of the 1988 Federal Constitution (Carvalho Almeida, 2020).The 1988 Constitution, when addressing freedom of expression (art. 5, IX) and freedom of journalistic information (art. 220), establishes that "no law shall contain any provision that may constitute an obstacle to the full freedom of journalistic information" and that "any and all censorship of a political, ideological, and artistic nature is prohibited" (art. 220, §2 and §3, II). Thus, the protection of freedom of information must be reconciled with the prohibition of anonymity and subsequent liability for any abuses (Barreto, 2024).Internationally, experiences such as that of the German NetzDG, which requires digital platforms to remove manifestly illegal content within 24 hours, offer models for regulatory responses. However, European legislation has evolved toward more balanced models, such as the European Union's Digital Services Act (DSA), which establishes obligations of transparency, proportional accountability, and respect for fundamental rights in content moderation practices. This approach seeks to avoid the risk of excessive removals that could constitute indirect censorship.The DSA introduces measures such as the obligation to provide periodic transparency reports, the requirement for clear explanations of the reasons for content removal, and the possibility of users to challenge the rules. The DSA seeks to balance combating disinformation with preserving freedom of expression. This model can inspire the Brazilian legal system, offering parameters of proportionality and due process in digital regulation.In Brazil, Bill No. 2630/2020 ("Fake News Bill") proposes the creation of transparency mechanisms for content moderation and the promotion of political propaganda, in addition to mandatory tracking of mass-forwarded messages. However, its wording still requires improvements, especially regarding the precise definition of "misinformation" and the provision of procedural guarantees against arbitrary removals (Barreto, 2024).It also highlights the need to regulate the activities of digital platforms, recognizing their role in mediating public debate. Transparency regarding ranking algorithms and content deletion policies is an essential condition for preserving a democratic information environment (França; Camarão, 2022).It is clear that the internet, far from remaining an unregulated space, has become the main battleground for truth, collective memory, and democratic values. Thus, combating disinformation requires digital governance that combines proportionate state regulation, responsible self-regulation, and active civil society participation (França; Camarão, 2022).Furthermore, any content monitoring and removal mechanism must observe due process, guaranteeing users the right to a full defense and to a rebuttal, as well as the existence of independent bodies for reviewing platform decisions. Strengthening media literacy, from the earliest stages of schooling, is also an indispensable measure for building a critical and resilient citizenry in the face of contemporary informational risks.FINAL CONSIDERATIONSThis study demonstrated that combating fake news is a complex task, requiring a balance between freedom of expression and the State's duty to protect the democratic order.  The impacts of fake news on public opinion formation compromise the electoral process, foster polarization, and undermine the public sphere as a place for rational debate.It is concluded that the State must intervene responsibly and proportionally, prioritizing educational actions, strengthening fact-checking institutions, and demanding greater accountability from digital platforms for the content they publish. At the same time, it is necessary to prevent measures to combat disinformation from becoming mechanisms for thought control. Therefore, it is recommended that clear and democratic legal frameworks be created, with independent oversight and civil society participation. Future studies may deepen the comparative analysis with other countries and evaluate the effects of regulatory policies on information freedom.REFERENCESBARRETO, Alana Maria Passos. Fake News, Financing, and Regulation of Social Networks: In Search of Harmonization. Public Law Journal, Brasília, v. 20, n. 2, 2023. Available at: https://www.portaldeperiodicos.idp.edu.br/direitopublico/article/view/7418. Accessed on: May 13 2025.CARVALHO ALMEIDA, . Fake News and Democracy: An Investigation of the Mechanisms for Controlling Disinformation in Brazil. Avant Journal, Florianópolis, v. 4, n. 2, p. 418–435, 2020. Available at: https://ojs.sites.ufsc.br/index.php/avant/article/view/6897. Accessed on: May 13. 2025.FRANÇA, Alexsandro José Rabelo; CAMARÃO, Felipe Costa. Regulating Fake News: National and International Regulations to Combat False News. GEI Journal, v. 8, n. 1, 2023. Available at: https://www.periodicojs.com.br/index.php/gei/article/download/826/653/3071. Accessed: May 13, 2025.RODRIGUES, T. M.; BONONE, L.; MIELLI, R. DISINFORMATION AND THE CRISIS OF DEMOCRACY IN BRAZIL: Is it Possible to Regulate Fake News?. Confluences. Interdisciplinary Journal of Sociology and Law, v. 22, n. 3, p. 30-52, December 2, 2020.
Keywords: Fake news; Public opinion; Democracy; Freedom of expression; State regulation